ELEMENTAL DEPTH PROFILE IN SEDIMENT CORE OF KORANGI CREEK ALONG KARACHI COAST, PAKISTAN - Chaudhry, M. Z.; Mashiatullah, A.; Javed, T.; Ahmad, N.; Khan, M. S.; Ahmad, N.; Qureshi, R. M. (The Nucleus, 2012)
In the present investigation downcore variation of metals such as Al, Ca, Cr, Cu, Fe, K, Mg, Mn, Ni, V and Zn in a sediment core of 42.5 cm length from Korangi Creek, one of the pollution hit sites along Karachi coast, was studied. Proton induced X-rays emission (PIXE) was the principal analytical technique used to detrermine the chemical composition in sediment core. Grain size analysis and sediment composition of cored samples indicated that Korangi Creek sediments is clayey in nature. Correlation matrix revealed strong association of Ni, Cu, Cr, Zn with Fe. To infer anthropogenic input, enrichment factors (EFs) were determined. EFs showed severe enrichment in surface sediments for Ni, Cu, Cr and Zn indicating increased industrial effluents discharge in recent years. If this trend of enrichment is allowed to continue unabated, it is most likely that the local food chain in this area may be adversely affected.